PENGARUH TOTAL ASET TURNOVER, DEBT TO EQUITY RATIO, RETURN ON EQUITY, DAN CURRENT RATIO TERHADAP RETURN SAHAM - Renaldo, Renaldo; Iskak, Jamaludin (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to find out and empirically prove the effect of total asset turnover, debt to equity ratio, return on equity, and current ratio on stock returns in consumer goods companies listed on the Indonesia Stock Exchange (IDX) in the 20182021 research period. The sampling method in this study was purposive sampling with a total sample of 30 data obtained from the financial statements of consumer goods companies opened by the IDX official website. The data processing in this study uses the Eviews version 12 program with the analytical tools used are multicollinearity test, multiple linear regression test, panel data model test, and hypothesis testing. The results showed that total asset turnover had a positive and significant effect on stock returns, but debt to equity ratio, return on equity, and current ratio had no effect on stock returns.